Additive Manufacturing Oriented Parametric Design Automation of Adaptive Joint System for an Irregular Form Gridshell Structure - Jin-Ho Ahn; Nam-Hyuk Ham; Ju-Hyung Kim; Jae-Jun Kim (Applied Sciences)
In architectural engineering, triangular tessellation using polygon mesh topology is one of the commonly used computational geometric approaches to simplify a free curved building façade into flat triangular facets and their subsequent straight edges. In such a façade system, exterior panels are supported by a network of profiles that correspond to their edges hidden behind the panels at an offset distance. A group of profiles, derived from the edges common to a node point of tessellated panels (i.e., the outermost panels enveloping the building), may dislocate from each other when offset from their original locations due to non-coplanar alignment and unique offset directions and distances. This dislocation problem gives rise to geometric complications in nodal connector design in addition to varying in the connected profile count and orientations. Design considerations regarding the effects of ’offset vertex dislocation’ (i.e., the dislocation of the edges when it offsets from the original topology due to incoherent normal direction) should incorporate proper variables in the correct sequence based on a fundamental understanding that causes the dislocation problem. However, it is very often these topological problems pertaining to offset that are neglected, leading to subsequent design flaws. Such oversights diminish the inherent strengths of DfMA (design for manufacture and assembly) and design automation. This study develops a computational mathematical approach aimed at addressing the geometric complexities in nodal connector design. It focuses on two main areas: the precise positioning of substructure profiles essential for the design and a design automation approach that minimizes the length of the nodal connector arms to enhance 3D printing productivity. A life-scale proof-of-concept structure based on an automated parametric design process that implements the research findings demonstrates the application, incorporating 3D-printed PA12 (Polyamide-12) nodal connectors.